Does digital transformation influence corporate financial flexibility reserves? A demand-side perspective - Liangliang Han; Fengchao Liu (Digital Economy and Sustainable Development)
Abstract The external business environment is increasingly characterized by volatility, uncertainty, complexity, and ambiguity (VUCA), heightening the critical role of financial flexibility in ensuring corporate survival and growth. Using a sample of Chinese A-share listed companies from 2011 to 2022, this study explores, from a demand perspective, whether and how corporate digital transformation affects financial flexibility reserves. The findings indicate that higher levels of digital transformation are associated with a reduced propensity and lower levels of financial flexibility reserves, suggesting that digital transformation significantly reshapes strategic financial resource allocation. By alleviating uncertainty and easing financing constraints, digital transformation diminishes the necessity for demand-driven financial flexibility reserves. Heterogeneity analysis reveals that the effect of digital transformation in reducing financial flexibility reserves is more pronounced among firms with low degrees of group affiliation, those without equity holdings in banks, and private firms. Furthermore, the study finds that digital transformation accelerates the speed and enhances the effectiveness of financial flexibility adjustments, optimizing resource allocation and enhancing the firm value. Therefore, corporate managers should align financial flexibility reserves with digital transformation strategies and the internal and external environment to maximize firm value.